2021
DOI: 10.3390/biom11081078
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Kidney—As Influenced by Heavy Metal Exposure and Selenium Supplementation

Abstract: The aging process in the kidneys has been well studied. It is known that the glomerular filtration rate (GFR) declines with age in subjects older than 50–60 years. However, there is still insufficient knowledge regarding the response of the aged kidney to environmental toxicants such as mercury, cadmium, and lead. Here, we present a review on the functional decline and proposed mechanisms in the aging kidney as influenced by metal pollutants. Due to the prevalence of these toxicants in the environment, human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 79 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…Among various metals, blood lead has been linked to blood homocysteine (48), an amino acid involved in oxidative stress and aging. Blood lead and blood mercury can affect kidney function through excessive production of ROS ( 49) and cause damage or apoptosis of renal tubular epithelial cells by destroying the balance of the oxidative stress system and heme oxygenase activity (9). Oxidative stress is considered an important mechanism of metal damage to renal function.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various metals, blood lead has been linked to blood homocysteine (48), an amino acid involved in oxidative stress and aging. Blood lead and blood mercury can affect kidney function through excessive production of ROS ( 49) and cause damage or apoptosis of renal tubular epithelial cells by destroying the balance of the oxidative stress system and heme oxygenase activity (9). Oxidative stress is considered an important mechanism of metal damage to renal function.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…Previous studies have shown (8) that heavy metals can promote the production of reactive oxygen species (ROS), oxidative stress, and kidney cell damage. Some researchers believe (9) that heavy metals can cause damage or apoptosis of renal tubular epithelial cells by destroying the oxidative stress system and in ammatory response-the balance of heme oxygenase activity, impairing renal tubular reabsorption and ultimately leading to Decreased kidney function. Therefore, oxidative stress is an essential mechanism of metal damage to renal function (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Mercury poisoning can cause hearing loss, gait abnormality, ataxia, erosive bronchitis, respiratory insufficiency, tremor, excitability (also known as mercurial erethism), loss of memory, insomnia, excessive salivation, tunnel vision, oxidative stress, kidney damage, lipid peroxidation and liver impairment. 23–26…”
Section: Introductionmentioning
confidence: 99%
“…Mercury poisoning can cause hearing loss, gait abnormality, ataxia, erosive bronchitis, respiratory insufficiency, tremor, excitability (also known as mercurial erethism), loss of memory, insomnia, excessive salivation, tunnel vision, oxidative stress, kidney damage, lipid peroxidation and liver impairment. [23][24][25][26] There is increasing interest in reducing the heavy metal concentration in aqueous medium using low molecular weight gelators. In some cases, the use of metal ions can trigger the formation of metallogels which can be useful in sensing as well as reducing their concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Aaseth et al [ 12 ], in a review, underscore the insufficient knowledge regarding the response of the aged kidney to environmental toxicants such as cadmium, mercury, and lead, and present proposed mechanisms of the aged kidney to metal pollutants. Human exposure to these toxicants is practically unavoidable in our industrialized society, and it may be hypothesized that exposure of individuals with reduced GFR will result in additional reductions in renal function.…”
mentioning
confidence: 99%